(untitled) (Bulletin of Pure and Applied Sciences – Physics, 2020)
In the present paper, we have measured and investigated the ultrasonic velocity (U), density ( ), viscosity ( ), adiabatic compressibility ( a ), intermolecular free length (Lf), molecular volume (Vm), available volume (Va), free volume (Vf), specific acoustic impedance (Z), Gibb’s free energy (G) in binary liquid mixtures of carbon tetra chloride and propyl ethyl Ketone (CCl4+PEK)] at 308.15K.